2008
DOI: 10.3174/ajnr.a1000
|View full text |Cite
|
Sign up to set email alerts
|

An Acute Ischemic Stroke Classification Instrument That Includes CT or MR Angiography: The Boston Acute Stroke Imaging Scale

Abstract: BACKGROUND AND PURPOSE:A simple classification instrument based on imaging that predicts outcomes in patients with actute ischemic stroke is lacking. We tested the hypotheses that the Boston Acute Stroke Imaging Scale (BASIS) classification instrument effectively predicts patient outcomes and is superior to the Alberta Stroke Program Early CT Score (ASPECTS) in predicting outcomes in acute ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 25 publications
0
64
0
2
Order By: Relevance
“…29 Proximal clot location is increasingly appreciated as an important determinant in outcome. 3,[30][31][32] Patients with a larger clot burden have been shown to have larger infarction volumes at baseline and poorer clinical outcomes. 33,34 The CBS is designed to be weighted to vessel location, assigning higher points to the terminal ICA and proximal MCA locations.…”
Section: Discussionmentioning
confidence: 99%
“…29 Proximal clot location is increasingly appreciated as an important determinant in outcome. 3,[30][31][32] Patients with a larger clot burden have been shown to have larger infarction volumes at baseline and poorer clinical outcomes. 33,34 The CBS is designed to be weighted to vessel location, assigning higher points to the terminal ICA and proximal MCA locations.…”
Section: Discussionmentioning
confidence: 99%
“…This population excluded TIA and is described in detail in Torres-Mozqueda et al 16 In 2005, 279 patients were identified who were admitted to the hospital from the emergency department with an admitting diagnosis of acute stroke. There were 15 patients who were excluded from the analysis because they had discharge diagnoses other than stroke (seizure, migraine, and neoplasia were the most common).…”
Section: Study Populationmentioning
confidence: 99%
“…16 Briefly, patients were classified as having a major stroke if by using either CT or MR angiography, a proximal cerebral artery occlusion was identified or when a large infarct was identified in a patient with patent major cerebral arteries. Proximal cerebral artery occlusion was defined as an occlusion of the distal (intracranial) internal carotid artery, the proximal (M1 or M2) middle cerebral artery, or the basilar artery.…”
Section: Patient Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Однако изолированная окклюзия ВСА (без вовлечения пе-редней хориоидальной артерии) независимо ассо-циирована с БФИ [56][57][58][59][60][61]. Установлено, что шкалы BASIS и CBS превосходят ASPECTS в отношении прогнозирования ФИ, при этом CBS имеет боль-шую чувствительность, а BASIS -специфичность [62][63][64][65]. ФИ напрямую коррелирует как со степе-нью коллатерального кровотока, так и реканализа-цией артерий, так как от них напрямую зависит КОИ [66][67][68][69][70].…”
Section: предикторы фи оии основанные на оценке состояния паренхимы unclassified